Rare immune diseases paving the road for genome editing-based precision medicine - Pavel-Dinu, Mara; Borna, Simon; Bacchetta, Rosa (Frontiers in Genome Editing, 2023)
CRISPR (clustered regularly interspaced short palindromic repeats) genome editing platform heralds a new era of gene therapy. Innovative treatments for life-threatening monogenic diseases of the blood and immune system are transitioning from semi-random gene addition to precise modification of defective genes. As these therapies enter first-in-human clinical trials, their long-term safety and efficacy will inform the future generation of genome editing-based medicine. Here we discuss the significance of Inborn Errors of Immunity as disease prototypes for establishing and advancing precision medicine. We will review the feasibility of CRISPR-based genome editing platforms to modify the DNA sequence of primary cells and describe two emerging genome editing approaches to treat RAG2 deficiency, a primary immunodeficiency, and FOXP3 deficiency, a primary immune regulatory disorder.